“Personalizing” Academic Medicine: Opportunities and Challenges in Implementing Genomic Profiling - Tweardy, David J. (2009)
BCM faculty members spearheaded development of a first generation Personal Genome Profile (Baylor PGP) assay to assist physicians in diagnosing and managing patients in this new era of medicine. The principles that are guiding the design and implementation of the Baylor PGP are high quality, robustness, low expense, flexibility, practical clinical utility and the ability to facilitate broad areas of clinical research. The single most distinctive feature of the approach taken is an emphasis on extensive screening for rare disease causing mutations rather than common risk-increasing polymorphisms. Because these variants have very large direct effects, the ability to inexpensively screen for them could have major immediate clinical impact in disease diagnosis, carrier detection, pre-symptomatic detection of late onset disease and even prenatal diagnosis. In addition to creating a counseling tool for individual ‘consumers’ this system will fit into the established medical record and be used by physicians involved in direct patient care. This paper describes an overall framework for clinical diagnostic array genotyping, and the available technologies as well as highlights the opportunities and challenges for implementation.